"Eu sou índia evangélica".: Um estudo sobre a adesão de mulheres pankaiwka ao pentecostalismo (Jatobá/PE) - Lima, Wellcherline Miranda (2019)
The Pankaiwka Indians, who live in the Volta do Moxotó District, in the Jatobá Municipality, in the Pernambuco Semiarid Region, a region called Sertão do São Francisco Sub-Midfield, have been inserted in the political and ethnic scene since 1999 with the recognition of the National Indian Foundation. The people were constituted through the migrations of the families of Pankararu, Jiripankó and Karuazu due to prolonged droughts and scarcity of land for work. The Pankaiwka people received from the Pankararu the cultural and religious legacy for their social organization. These people often make interethnic contact with other indigenous and non-indigenous peoples, in addition to the approximation of urban centers and access to the media that has caused changes in the religious aspect in the territory. The changes have occurred as there is a great offer of meanings for subjects, new religious experiences that impact the ways of interacting in the social sphere. This led to the emergence of new meanings for some Pankaiwka indigenous women, who self-affirm themselves as “evangelical India” and have adhered to Pentecostalism. This new religious experience has a different structure from the traditional religion of its people. At the same time that the Indians have re-signified their beliefs, the religion of tradition, and the religion adhering to the Pentecostal, promote the reformulation of the ethnic frontier. The fact is reflected in an active and complex religious mobilization that is part of the Brazilian religious field. The research aimed to analyze the adherence of Pankaiwka indigenous women to Pentecostalism from the narratives that express the religious experiences of the subjects in the research field. The theoretical framework was supported by indigenous peoples in the Northeast, the Pankararu people, who are ancestors of the Pankaiwka, the Pankaiwka people, indigenous women and Pentecostalism. The conceptual contribution came from the discussions about identity, culture, religion and ethnic frontier. The qualitative methodological course began with the bibliographic survey to study and systematize the themes and concepts; and in parallel to the field research with semi-structured interviews with Caciques, Pajé, Trader, Prayers, Mother of Folguedo, farmers to understand the history, culture, socio-environmental calendar and indigenous tradition in Pankaiwka. And in the second part of the interview, with women who joined Pentecostalism. The method of study of the collected data was analysis of the interviews. After studying the bibliographic materials and data from the research field, it was evident that Pankaiwka women, who adhered to Pentecostalism, promote a religious resignification, identifying themselves as “evangelical India”, with the recognition of the leadership of their people to continue its Pentecostal religious experience, promoting the reformulation of the ethnic frontier.